Median sternotomy versus intercostal thoracotomy for lung lobectomy: A comparison of short‐term outcome in 134 dogs. Issue 1 (10th November 2017) - Bleakley, Seth; Phipps, Kevin; Petrovsky, Brian; Monnet, Eric
Abstract: Objective: To compare short‐term outcomes between dogs undergoing lung lobectomy via median sternotomy (MS) or intercostal thoracotomy (ICT). Study design: Retrospective case control study. Methods: Medical records of dogs that underwent lung lobectomy via MS or ICT at a single institution were reviewed for demographics, intraoperative findings, and postoperative management and outcomes. Dogs with pleural effusion, pneumonia, migrating foreign body, lung abscess, spontaneous pneumothorax, or lung lobe torsion were excluded. Short‐term outcome factors up were compared up to the time of death, euthanasia, or discharge from the hospital. Results: One hundred and thirty‐four dogs met the inclusion criteria. Forty‐one (31%) dogs underwent MS and 93 dogs (69%) underwent ICT. Fluid production from the chest tube ( P  = .0061), alveolar arterial pressure gradient ( P = .0001), and complications requiring intervention ( P  = .0245) were more common in the MS group than the ICT group. Pain management and all other short‐term outcome factors did not differ between procedures. Five dogs from the MS group and 4 from the ICT group were euthanized in the postoperative period ( P  = .0925). Conclusion: In a surgical procedure that does not preclude either approach, ICT may be more desirable than MS in terms of postoperative pain, oxygenation, and complications. However, since no other short‐term measure of outcome differed, we can state that both MS and ICT are well tolerated by dogs.